Implementasi Pendidikan Karakter Melalui Pembiasaan pada Anak Usia Dini: Studi Kasus di TK Bintang Kecil Bogor - Farah Chalida Hanoum (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to describe the implementation of character education through habituation which includes planning, implementing, evaluating the results of character education, supporting factors and inhibiting the implementation of character education through habituation in Bintang Kecil Kindergarten Bogor. This research method uses a qualitative approach with a qualitative descriptive method. Data collection techniques were conducted by interview, observation, and documentation. The results of this study indicate that the process of character education through habituation is carried out by students according to the stages, namely planning, implementation, evaluation and results as well as supporting factors and inhibiting factors. The planning of children's character education is carried out through daily habits in accordance with 9 of the 18 values ​​of the nation's character, namely religious, honest, tolerance, discipline, creative, curious, friendly/communicative, fond of reading and caring for the environment. The implementation includes the process of implementing character education in everyday life through the habituation given by teachers to children. humans, morals of worship by carrying out activities that support Keywords: character education, early childhood.